Sensor-driven analysis of angle of attack in alpine skiing: a laboratory exploration - Schütz, S.; Thorwartl, C.; Thorwartl, P.; Stöggl, T.; Holzer, H. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
The aim was to address the absence of a universal measuring instrument for detecting the degree of carving or skidding in a ski turn. Sensors were employed to calculate the so-called angle of attack (Theta), which increases if lateral skidding increases. A mathematical concept in 2D and 3D for sensor-based detection of the Theta was developed and evaluated on a self-built centrifugal machine capable of executing both optimal carving as well as certain degrees of skidding. The variation of Theta was systematically divided into the stages small, medium, and large. Each stage was further subdivided into three smaller levels to evaluate the discriminability of minor changes. Across all settings with different Theta values, both 2D and 3D methods demonstrated precise recording and discrimination of subtle differences (1°-1.5°), as confirmed by 95%-Confidence Intervals.